O particípio presente como modificador do sintagma nominal da língua inglesa: uma análise de dados de um corpus de aprendizes brasileiros - Stefânia Aparecida de Lima Silva (2021)
This research seeks to describe academic writing in texts produced by Brazilian English learners, in comparison with written productions by native American and British speakers, regarding the use of pre- and post-modifiers of the English noun phrase performed by present participle -ing, a non-finite form of the verb. For finding occurrences of these modifiers, two corpora were used: the CorIsF-English (Corpus of English without Borders), the study corpus, and the LOCNESS (Louvain Corpus of Native English), the reference corpus. In order to carry out the quantitative and qualitative comparative analysis of the data and to find, in the corpora, specific patterns of use of -ing as a pre or post-modifier, the AntConc software was used. For data comparison, the grammatical concepts of pre- and post-modifiers were used in English and in Portuguese. The present participle performs the syntactic function of post-modifier of the noun phrase in both languages; however, this non-finite form of the verb only occurs as a pre-modifier in English. This study was based on the hypothesis, which was confirmed, that a higher numerical density of occurrences with post-modifiers would be found in the writing of Brazilian learners in relation to occurrences of pre-modifiers. Furthermore, certain patterns of use of post-modifiers found in the learners' production are similar to patterns found in formal grammars of the Portuguese language, what we suggest are cases of language transfer from the mother tongue of these speakers due to a learning strategy.